Virtual Cohorts and Synthetic Data in Dementia: An Illustration of Their Potential to Advance Research - Muniz-Terrera, Graciela; Mendelevitch, Ofer; Barnes, Rodrigo; Lesh, Michael D. (Frontiers in Artificial Intelligence, 2021)
When attempting to answer questions of interest, scientists often encounter hurdles that may stem from limited access to existing adequate datasets as a consequence of poor data sharing practices, constraining administrative practices. Further, when attempting to integrate data, differences in existing datasets also impose challenges that limit opportunities for data integration. As a result, the pace of scientific advancements is suboptimal. Synthetic data and virtual cohorts generated using innovative computational techniques represent an opportunity to overcome some of these limitations and consequently, to advance scientific developments. In this paper, we demonstrate the use of virtual cohorts techniques to generate a synthetic dataset that mirrors a deeply phenotyped sample of preclinical dementia research participants.